LITERATURE REVIEW: THE INFLUENCE OF DETERMINANTS OF MSME TAX COMPLIANCE - Sadono Mulyo; Evelyne Shafina; Ayuwinarti Purba; Indra Pahala; Puji Wahono (JURNAL ILMIAH EDUNOMIKA, 2024)
Tax compliance in Micro, Small, and Medium Enterprises (MSMEs) is crucial in strengthening state revenue and creating a conducive business environment. This study employs a literature review method to explore the factors influencing tax compliance in MSMEs, referring to various previous studies conducted in the same domain. The analysis results state that several factors, including economic aspects, knowledge, awareness, trust, policies, social aspects, and technology, have a significant influence. These findings indicate that policy, knowledge, and economic factors play a crucial role in determining the level of tax compliance in MSMEs. Therefore, the recommended recommendations include improving the effectiveness of tax law enforcement, simplifying the payment process, intensifying education programs, and providing incentives to tax-compliant MSMEs.